Public Support for Plea-Bargaining in Serious Economic Crimes in Indonesia: Compatibility of Current and Modified Plea-Bargaining Models - Febby Mutiara Nelson; Pricilla Amelinda Jacob; Haykal Hafizul Arifin (Faculty of Law, Sriwijaya University, Indonesia, 2026)
The incorporation of plea bargaining into Indonesia’s Criminal Procedure Code has generated debate regarding its suitability for serious economic crimes. While existing discussions have primarily focused on its compatibility with Indonesian criminal procedure, empirical research examining public attitudes toward plea bargaining in Indonesia remains limited. Using survey data collected through non-probability sampling, the study compares public support for the conventional criminal justice system, restorative justice approaches, the restricted and a modified plea bargaining models. The findings demonstrate that respondents expressed greater support for the modified plea-bargaining model than for other mechanisms. Grounded in Cognitive Continuum Theory, the findings demonstrate that support for plea bargaining is shaped by the quasi-rational mode of cognition, whereby individuals rely on both moral evaluations of punishment and rational assessments of whether the punishment is proportionate to the offender’s actions and their impact on victims.